Stanovanjska ranljivost v Mestni občini Ljubljana - Filipovič Hrast, Maša (Urbani izziv, 2007)
Vulnerable groups are defined as groups that have fewer resources than other population groups and are therefore in a deprivileged position from the beginning. One of important areas of vulnerability, which influences importantly individuals lives and lives of whole families, is the housing area. Institutional, structural, as well as personal and relational factors influence housing vulnerability. It is also something that touches very different population groups. In the article we analyse housing conditions of vulnerable groups in the Municipality of Ljubljana. We focus on the following vulnerable groups: single parent households, households with children, older people and low income groups. The economic situation of vulnerable groups is portrayed and their housing strategies for improving their housing situation are described. The results of the analysis indicate that specific support measures are needed for vulnerable households in homeownership status. The article also warns of the danger of development of wrack-renting, i.e. rentingof low quality, low cost dwellings.
Keywords: družbena diferenciacija; družbene skupine; Ljubljana; ogroženost; stanovanja; stanovanjska politika; stanovanjsko vprašanje